Identification of ex vivo marker for improvement in detectability of synthetic peptides in human urine - Heo, Soohyun; Cho, Yoeseph; Park, Hana; Lee Hyun Jeong; Park, Saeyeon; Hwang, Sungmin; Moon, Jihwan; Jung, Hyungil; SON, Jung hyun (제73회 한국분석과학회 추계학술대회 [초록집], 2024)
The list of prohibited substances provided by the World Anti-Doping Agency (WADA) includes peptides hormones and their releasing factors. These molecules face challenges in detection as it is known to have short half-life and its similar structure to natural substances. Additionally, these molecules are susceptible to external factors such as temperature and time, which can cause degradation. The potential degradation of the substances in urine samples has been considered, as these external factors pose significant challenges in detection. This study aimed to improve the detectability of synthetic peptides by suggesting a tracker of prohibited drugs. Sample transportation, one of preanalytical variables, has been considered and the scenario of external factors impacting the samples in the procedure has been applied in the experiment. In the previous study, GHRP-2, GHRP-6, and Hexarelin were selected and was observed to decrease in peak area under this condition. An altered product was found in prior research, which could be used as a marker for prohibited substance. In this study, the altered product found in the human urine were identified by collecting characteristics of the altered products, using urea solution, and utilizing Q-Exactive mass spectrometry. The altered product was identified as carbamylated product and tested to be used as ex vivotracker of prohibited drug. This finding aims to extend the application further to other prohibited substances, providing a new avenue for anti-doping detection and sample availability.